2011
DOI: 10.1007/s00134-010-2127-7
|View full text |Cite
|
Sign up to set email alerts
|

Improved survival in severe paraquat poisoning with repeated pulse therapy of cyclophosphamide and steroids

Abstract: Repeated pulses of CP and MP, rather than high doses of CP and DEX, may result in a lower mortality rate in patients with severe PQ poisoning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 26 publications
2
77
0
1
Order By: Relevance
“…[34] Current treatment of PQ poisoning focuses on reducing the absorption of PQ from the gastrointestinal tract and increasing its elimination. [32] Even though activated charcoal was used to treat PQ toxication,[14] evidence was not enough to confirm that charcoal can improve the prognosis of patients. Since the therapeutic effect of smecta on rats with PQ toxication has rarely been studied, we tried to explore whether smecta can reduce the PQ plasma concentration and improve the pathological changes of rats after PQ poisoning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[34] Current treatment of PQ poisoning focuses on reducing the absorption of PQ from the gastrointestinal tract and increasing its elimination. [32] Even though activated charcoal was used to treat PQ toxication,[14] evidence was not enough to confirm that charcoal can improve the prognosis of patients. Since the therapeutic effect of smecta on rats with PQ toxication has rarely been studied, we tried to explore whether smecta can reduce the PQ plasma concentration and improve the pathological changes of rats after PQ poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…[11–13] Studies[1416] focus mostly on gastric lavage, blood purification, glucocorticoid and cyclophosphamide, but there are different opinions on these methods. It was reported that to prevent the absorption of PQ by the gastrointestinal tract, patients were administered with activated charcoal in 250 mL magnesium citrate via a nasogastric tube,[14] suggesting that superactive adsorbent is beneficial to reduce blood concentration.…”
Section: Introductionmentioning
confidence: 99%
“…It is impossible for us stop person making use of paraquat, but some new therapy must be considered to control paraquat poisoning. Paraquat poisoning could not be controlled by only one method and combined therapies are needed (Lin et al, 2011). So, it was hypothesized in this study that whole lung lavage will provide a new therapy of acute lung injury caused by paraquat.…”
Section: Hypothesismentioning
confidence: 99%
“…1 Attempts to modify the toxicity of paraquat have proven ineffective, and the clinical outcome of poisoning is therefore determined by degree of exposure. [2][3][4][5][6] The primary mechanism of exposure is ingestion, after which paraquat accumulates primarily in the lungs, resulting in acute pulmonary distress. 7 The selective accumulation of paraquat in alveolar cells induces the production of large quantities of toxic free radicals such as reactive oxygen species, leading to lipid peroxidation of cell membranes, exhaustion of nicotinamide adenine dinucleotide phosphate and cell death.…”
Section: Introductionmentioning
confidence: 99%
“…HP is most effective when initiated within 2 h of paraquat injection and 4 h of ingestion and administered continuously for 6-8 h. 11,12 HP is of limited value in cases of severe paraquat poisoning, however. 13,14 Repeated pulses of immunosuppression with methylprednisolone and cyclophosphamide may lower mortality rates, 5 although a multicentre study found that mortality rates remained high in spite of large intercentre variations in treatment (including HP, immunosuppression and antioxidant treatment). 4 Continuous renal replacement therapy, such as continuous venovenous haemofiltration (CVVH), is used to treat patients with acute renal failure and cardiovascular instability and is believed to eliminate excess cytokines and inhibit abnormal enzyme release.…”
Section: Introductionmentioning
confidence: 99%